UTILIZATION OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN ONLINE LEARNING IN EDUCATIONAL INSTITUTIONS - Dastur Fadli (Jurnal Penelitian Progresif, 2024)
The rapid development of Information and Communication Technology (ICT) has had a significant impact on various aspects of life, including education. Online learning, which utilizes digital technology for the teaching and learning process, has become an increasingly popular alternative in the digital era. This study uses a qualitative method with a case study approach. This research was conducted in an Educational Institution, with data collection techniques in the form of interviews, observation, and documentation. The results of the study indicate that, the Utilization of Information and Communication Technology (ICT) in online learning in Educational Institutions is carried out in various ways, such as: Online Learning Platforms, Learning Videos, Live Streaming and Video Conferences, Educational Applications, Digital Learning Materials, Use of Social Media, Online Evaluation and Online Counseling. Several factors that support the effectiveness of online learning in Educational Institutions include: Adequate ICT Infrastructure, Teacher Training, Adapted Curriculum, Interactive Learning Content, Technical and Administrative Support, Parental Participation, Effective Collaboration and Communication, Comprehensive Assessment, Flexibility and Differentiation and Continuous Evaluation and Improvement. There are several factors that can hinder the effectiveness of online learning in educational institutions, including: Limited access to technology, limited technological skills and knowledge , limited interaction and collaboration, technical disruptions and unstable internet connections, lack of student motivation and engagement, lack of support from parents or guardians, isolation and emotional well-being, inability to facilitate practical work or live demonstrations, lack of constructive evaluation and feedback, and inequality of access and opportunities.